Planning of Reserve Branches to Increase Reconfiguration Capability in Distribution Systems: A Scenario-Based Convex Programming Approach - Tabares, Alejandra [UNESP]; Puerta, Gabriel F. [UNESP]; Franco, John F. [UNESP]; Romero, Ruben A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Distribution networks are usually designed with a fixed tree-shape topology, which limits its adapting capability against failures and excessive variation of load/generation. Reconfiguration is an important tool to optimize the steady-state operating point of the distribution system under normal operating conditions, as well as increasing the network's responsiveness under interruptions by minimizing non-supplied demand. This paper studies how to increase the capabilities of reconfiguration in distribution networks through the optimal installation of reserve branches even if few branches are switchable. For this purpose, a scenario-based convex programming model is proposed to minimize the operation cost under normal operating conditions along with the energy not supplied related to network interruptions. Instead of conventional simulation adopted by previous approaches, the formulation is based on a set of linear logical constraints that represent the post-fault network reconfiguration process. Hence, classical optimization techniques can be used to solve the proposed model, which provides a suitable framework for the attainment of global optimality using efficient off-the-shelf software. Results show a decrease in the cost of energy production (2.85% and 1.08% for the 33-node and 69-node test systems) along with a decrease in the cost of energy not supplied (58.17% and 72.42% for the 33-node and 69-node test systems) due to the greater restoration capacity of the system using reserve branches.
Keywords: Convex programming; post-fault reconfiguration; reconfiguration; restoration